Nanostructural Sc-based hierarchy to improve the creep resistance of Al–Cu alloys. (15th January 2020) - Yang, Chong; Cao, Lingfei; Gao, Yihan; Cheng, Pengming; Zhang, Peng; Kuang, Jie; Zhang, Jinyu; Liu, Gang; Sun, Jun
Abstract: Al-2.5 wt% Cu alloys with different Sc additions (0, 0.1, 0.3, 0.5 wt%) are studied in comparison to reveal the Sc microalloying effect on precipitation, room temperature mechanical properties, and creep resistance. The results show that the Sc addition into the Al–Cu alloys can effectively promote the precipitation of θ′ -Al2 Cu, reducing the size and narrow the size distribution. However, the Sc-dependences of mechanical properties at room and at high temperatures are much different. Although the 0.3 wt% Sc addition results in the densest homogeneous θ′ -Al2 Cu precipitation and hence the highest room temperature strength, the 0.5 wt% addition leads to the most improved creep resistance at 300 °C that is derived from a nanostructural Sc-based hierarchy, i.e., Al3Sc dispersoid/heterogeneous θ′ -Al2 Cu precipitate units, homogeneous θ′ -Al2 Cu precipitates, strongest Sc segregation at θ′ /matrix interfaces, and Sc clusters. The nanostructural hierarchy with thermally resistant nanostructural features at different length scales provides a new way to develop advanced Al alloys with excellent high-temperature stability and mechanical properties. The strengthening mechanisms at room and high temperatures are respectively discussed. Graphical abstract: Image 1 Highlights: The Sc addition have a remarkable microalloying effect on the microstructures and mechanical properties of Al–Cu alloys. The Sc-dependences of mechanical properties at room and at high temperatures are much different. A nanostructural Sc-based hierarchy enhanced creep resistance is confirmed and the strengthening mechanisms are unraveled.